"Whatever it takes" to resolve the European sovereign debt crisis? Bond pricing regime switches and monetary policy effects. (September 2018) - Afonso, António; Arghyrou, Michael G.; Gadea, María Dolores; Kontonikas, Alexandros
Highlights: We estimate TVP panel models capturing regime shifts in EMU sovereign bond markets. We then model the impact of ECB policies on the risk factor sensitivities of spreads. We find a new pricing regime following the announcement of the OMT programme. Unconventional monetary policy measures also affect the pricing of sovereign risk. Overall, ECB actions have reversed the dynamics of the euro sovereign debt crisis. Abstract: This paper investigates the role of unconventional monetary policy as a source of time-variation in the relationship between sovereign bond yield spreads and their fundamental determinants. We use a two-step empirical approach. First, we apply a time-varying parameter panel modelling framework to determine shifts in the pricing regime characterising sovereign bond markets in the euro area over the period January 1999 to July 2016. Second, we estimate the impact of ECB policy interventions on the time-varying risk factor sensitivities of spreads. Our results provide evidence of a new bond-pricing regime following the announcement of the Outright Monetary Transactions (OMT) programme in August 2012. This regime is characterised by a weakened link between spreads and fundamentals, but with higher spreads relative to the pre-crisis period and residual redenomination risk. We also find that unconventional monetary policy measures affect the pricing of sovereign risk not only directly, but also indirectly through changes in banking risk. Overall, the actions of the ECB have operated as catalysts for reversing the dynamics of the European sovereign debt crisis.